GRAMMAR ASSESSMENT USING THE QUIZIZZ APPLICATION (A Case Study Class XI at SMK Bina Bangsa Ciledug Kota Tangerang) - Nurul Kholifah; Abdul Muin; Selnistia Hidayani (Al-Shobar Publisher, Yayasan Islam Al-Shobar Rawaurip, 2024)
This research aims to identify and analyze how teachers use the Quizizz application to assess grammar tests. Then this research also aims to identify the obstacles faced by students when using the Quizizz application. This research uses a case study method, using interviews and questionnaires with teachers and students. Researchers found that 100% of teachers agreed to use the Quizizz application with various advantages of the application, namely it is practical, effective, efficient and does not take a long time. Researchers found that there were four obstacles faced by students, 53.3% of students had difficulty accessing the internet due to inadequate facilities at school and the facilities that students had. Then 50% of students had problems with the language display in the Quizizz application, caused by the students' lack of vocabulary. Furthermore, 46.7% of the obstacles were the lack of question-and-answer activities between students and teachers, this had an impact on students' difficulty working on questions because they thought it was difficult to ask the teacher. Then 43.3% had problems using the Quizizz application, the cause was students' lack of technological knowledge.